2019
DOI: 10.1101/715318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifaceted adaptation of the neural decision process with prior knowledge of time constraints and stimulus probability

Abstract: When selecting actions in response to noisy sensory stimuli, the brain can exploit prior knowledge of time constraints, stimulus discriminability and stimulus probability to hone the decision process, but the full range of underlying neural process adjustments remains to be established. Here, we draw on human neurophysiological signals reflecting decision formation to construct and constrain a multi-tiered model of priorinformed motion discrimination, in which a motor-independent representation of cumulative e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(110 reference statements)
1
2
0
Order By: Relevance
“…No such differences were observed for the window 800–1600 ms (t(18)=1.12, p=0.28; all p>0.1 for t-tests on contra-ipsi lateralisation in contiguous 50 ms bins from 800 ms to 1600 ms). This observation accords with recent demonstrations that prior-infromed motor level adjustments do not impact on the CPP process (Steinemann et al, 2018; Kelly et al, 2019).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…No such differences were observed for the window 800–1600 ms (t(18)=1.12, p=0.28; all p>0.1 for t-tests on contra-ipsi lateralisation in contiguous 50 ms bins from 800 ms to 1600 ms). This observation accords with recent demonstrations that prior-infromed motor level adjustments do not impact on the CPP process (Steinemann et al, 2018; Kelly et al, 2019).…”
Section: Resultssupporting
confidence: 93%
“…First, the evidence-dependent build-up of the CPP has been shown to reliably precede that of motor preparation signals (Kelly and O'Connell, 2013). Second, it has been shown across several studies that the CPP and motor signals undergo distinct strategic adjustments: premotor Mu/Beta-band activity contralateral to the decision reporting effector always reaches a stereotyped threshold level prior to response execution but both contralateral and ipsilateral signals exhibit systematic shifts in their starting levels in response to prior information about time constraints (Steinemann et al, 2018) and stimulus probability (Kelly et al, 2019), as well as a temporally increasing urgency component to their build-up (Murphy et al, 2016; Steinemann et al, 2018; Kelly et al, 2019). In contrast, the CPP has been found to not change its starting level and its pre-choice amplitude varied systematically as a function of RT for discrete decisions with a time limit (Steinemann et al, 2018; Kelly et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A crucial signature of evidence accumulation is that the corresponding signal peaks close to the time of the response, with that peak occurring earlier for faster compared to slower decisions. This is frequently observed for the CPP in perceptual decision making when the onset of the relevant stimulus is purposefully obscured, thus when the subjective onset of the stimulus can vary relative to the objective onset (Kelly, Corbett, & O’Connell, 2021; Kelly, Corbett, & O’Connell, 2019; Kelly & O’Connell, 2013; Pereira et al, 2021). However, other decision-making studies that have identified the CPP as a signature of evidence accumulation only show response-locked activity (Boldt et al, 2019; Pisauro et al, 2017); and in some cases where stimulus-locked activity was examined, including our present results, the expected latency effect was not found (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 87%